New records and an updated list of reptiles from Thanh Hoa Province, Vietnam - Vinh Dau; Thao Hoang; Truong Nguyen; Anh Pham (Biodiversity Data Journal)
Thanh Hoa Province is located in North Central Vietnam and the Province contains a large area of 393,361.33 hectares of natural forest. A complexity of landforms has given this Province a high level of biodiversity potential. However, the reptile fauna of Thanh Hoa Province is still underestimated. Previous studies documented 111 species of reptiles from this Province.As a result of our field surveys in Pu Luong and Xuan Lien Nature Reserves, we report five species of reptiles for the first time from Thanh Hoa Province, Vietnam, namely Plestiodon tamdaoensis, Scincella devorator (Scincidae), Elaphe taeniura, Pareas macularius and Pseudoxenodon macrops (Colubridae), with novel data about morphological characteristics. In addition, we provide an updated checklist of 116 species of reptiles from Thanh Hoa Province. The reptile fauna of Thanh Hoa Province also contains a number of species of conservation concern: 22 species listed in the Red Data Book of Vietnam, 22 species listed in the IUCN Red List, 18 species listed in the Vietnam Governmental Decree No. 84; and 21 species listed in CITES appendices.